Marine in the Qur'an: Interpretation of Al-A’raf verse 57 and Ar-Rahman verses 19-20 - Muhamad Fajar; Muhamad Lutfi Puadi; Qama Ramadhan; Yusran Anshar Musyaffa; Bannan Naelin Najihah (Journal of Ulumul Qur'an and Tafsir Studies, 2023)
[Ocean in the Qur'an: Interpretation Study of Ar-Rahman verses 19-20] Indonesia is an archipelagic country with a traffic lane that connects the Pacific Ocean and the Indian Ocean. The sea is a natural wealth with various phenomena and biota in it. There are various signs in the verses of the Qur'an about natural phenomena that occur in the world, one of which is the phenomenon of the meeting of two seawaters but they do not mixing each other. This phenomenon deserves to be researched because of the rarity of studying discussions regarding this in the community. So this study aims to provide knowledge to the public regarding natural phenomena in the Qur'an. This study uses a descriptive method by collecting various references from the marine sector and interpretive studies about natural phenomena in the Qur'an. The discovery of the phenomenon of two sea waters that do not mix with each other proves the truth of the word of Allah SWT. Hopefully, this research will provide readers with an understanding of this phenomenon and this research study of commentary will become one of the evidences of the truth of the Qur'an and have an impact on science, especially in the marine sector.